Data and Information Systems Management for the Urban Water Infrastructure Condition Assessment - Carriço, Nelson; Ferreira, Bruno (Frontiers in Water, 2021)
Most of urban water infrastructure around the world were built several decades ago and nowadays they are deteriorated. So, the assets that constitute these infrastructures need to be rehabilitated. Since most of the assets are buried the water utilities face the challenge to decide how, where and when to rehabilitate. Therefore, condition assessment is vital to plan rehabilitation actions and is mostly based on the data collected from the networks. This collected data need to be put together in order to be transformed into useful information. Nonetheless, the large amount of assets and data involved makes data and information management a challenging task for water utilities. This paper highlights the importance of data and information systems’ management for urban water infrastructure condition assessment.